PERANAN SATUAN POLISI PAMONG PRAJA DALAM PENGAWASAN MINUMAN BERALKOHOL DI KOTA PADANG - Roby Gandareva dan Meita Lefi Kurnia (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
After the implementation of the Padang City Regional Regulation No. 8 of 2012 concerning Supervision, Control and Prohibition of Alcoholic Drinks has implications for the circulation of alcoholic drinks in the City of Padang. The Civil Service Police Unit as a regional apparatus in carrying out its duties has a supervisory function over the community, apparatus, or legal entity for the implementation of Regional Regulations and Regional Head Regulations. Satpol PP in supervising alcoholic drinks in the city of Padang is carried out against 1) Direct sellers or retailers of alcoholic drinks of class B and / or C, or alcoholic drinks containing spices, herbal medicine and / or the like, 2) Sales and / or packaging of drinks class B and / or class C alcoholic drinks, 3) The location for storing or selling alcoholic drinks of class B and / or class C. As for the constraints of the role of the civil service police unit in monitoring alcoholic drinks in Padang city, namely: 1) Limited number of personnel and facilities making the Satpol PP of Padang City in supervising alcoholic drinks not maximally, 2) There is resistance by direct sellers or retailers of alcoholic drinks, 3) Business actors who have been repeatedly disciplined are still carrying out activities to sell alcoholic drinks. How to Overcome Obstacles From the Role of Civil Service Police Units in Supervision of Alcoholic Drinks in Padang City, namely: 1) Padang City Satpol PP tries to meet the number of personnel and facilities needed by recruiting personnel and purchasing facilities, 2) Padang City Satpol PP continues supervise alcoholic beverage sales places that are not in accordance with the provisions in a humane and professional manner, 3) Satpol PP will continue to supervise alcoholic drink sellers consistently and continuously.